2007
DOI: 10.1016/j.thromres.2007.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the β-fibrinogen Hae III and factor XIII Val34Leu gene variants with venous thrombosis

Abstract: Introduction-The factor XIII Val34Leu (100 G→T) and β-fibrinogen Hae III (-455 G→A) gene variants have been associated with reduced risk of venous thrombosis, but not in all studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Interaction between Ox40 on T cells and Ox40L on vascular endothelial cells induces the production of RANTES (regulated on activation, normal T expressed and secreted), which recruits more T cells to the endothelium, thereby promoting a local proinflammatory state (22 ). The present data further highlight the potential involvement of inflammation in the pathogenesis of VTE in addition to the commonly perceived coagulation and fibrinolytic mechanisms (23)(24)(25).…”
Section: Discussionsupporting
confidence: 52%
“…Interaction between Ox40 on T cells and Ox40L on vascular endothelial cells induces the production of RANTES (regulated on activation, normal T expressed and secreted), which recruits more T cells to the endothelium, thereby promoting a local proinflammatory state (22 ). The present data further highlight the potential involvement of inflammation in the pathogenesis of VTE in addition to the commonly perceived coagulation and fibrinolytic mechanisms (23)(24)(25).…”
Section: Discussionsupporting
confidence: 52%
“…In a meta-analysis of retrospective studies involving 3165 cases, the factor XIII Val34Leu polymorphism, which is associated weakly with higher factor XIII activity but not with subunit levels, was inversely associated with VTE risk, but this was not confirmed in the subsequently published LITE study, which had the largest sample size of studies to date. 11 A mutation in the factor XIII B-subunit, the carrier for the factor XIII A-subunit, leads to increased dissociation of factor XIII in plasma and has also been related to modestly increased thrombosis risk. 33 Strengths of our study include the prospective design, with coagulation factors almost always measured before occurrence of events.…”
Section: Discussionmentioning
confidence: 99%
“…5 An inverse association of factor XIII (activity and the Val 34 Leu polymorphism) with VTE has been reported, but results for the factor XIII gene variant have been mixed. 10,11 In a study of postoperative asymptomatic deep vein thrombosis (DVT), higher factor VIII, but not factors VII or IX, was associated with DVT risk. 12 Confirmation of these results in other populations, preferably in prospective studies, is important for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been conducted to discover the link between Val34Leu Polymorphism and venous Thrombosis, some studies have been shown that the Lue34 variant was associated with a decreased risk of venous thrombosis [14,15] but other studies have been shown conflicting results [13,16,17,18].…”
Section: Introductionmentioning
confidence: 99%